New hydrazide–hydrazones of isonicotinic acid: synthesis, lipophilicity and in vitro antimicrobial screening. (5th January 2018) - Popiołek, Łukasz; Biernasiuk, Anna; Berecka, Anna; Gumieniczek, Anna; Malm, Anna; Wujec, Monika
Abstract : This study describes the synthesis, lipophilicity and in vitro antimicrobial assays of 15 new hydrazide–hydrazones of isonicotinic acid. New derivatives were obtained on the basis of the condensation reaction of isonicotinic acid hydrazide with different aromatic aldehydes. The chemical structure of synthesized compounds was confirmed by spectral methods. Experimental lipophilicity of new isonicotinic acid derivatives was determined using reversed‐phase thin‐layer chromatography. All synthesized compounds were subjected to in vitro antimicrobial assays against reference strains of Gram‐positive bacteria, Gram‐negative bacteria and fungi belonging to Candida spp. Some of the synthesized hydrazide–hydrazones proved to be significant antibacterial compounds and more potent than commonly used chemotherapeutic agents. Abstract : This study describes the synthesis, lipophilicity and in vitro antimicrobial assays of 15 new hydrazide–hydrazones of isonicotinic acid. New derivatives were obtained on the basis of the condensation reaction of isonicotinic acid hydrazide with different aromatic aldehydes. The chemical structure of synthesized compounds was confirmed by spectral methods. Experimental lipophilicity of new isonicotinic acid derivatives was determined using reversed‐phase thin‐layer chromatography. All synthesized compounds were subjected to in vitro antimicrobial assays against reference strains of Gram‐positive bacteria, Gram‐negative bacteria and fungi belonging to Candida spp. Some of the synthesized hydrazide–hydrazones proved to be significant antibacterial compounds and more potent than commonly used chemotherapeutic agents.